Learning to Sell Sex(ism) Advertising Students and Gender - O'Driscoll, Aileen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book presents the first in-depth exploration into the gendered attitudes and worldviews of advertising students. Offering a significant contribution to other cultural sociological works concerning the cultural and creative industries, Learning to Sell Sex(ism) adds further weight to the argument that it is imperative that we look closely at the people who create media texts in order to better account for and challenge sexist media content. In this study, such media creators are the advertising industry's next generation of practitioners and creatives. Involving a mix of in-depth questionnaires, qualitative surveys, interviews with students, observational data, as well as an examination of the components comprising advertising modules, O'Driscoll documents the dominant gendered discourses articulated by advertising students and offers an opportunity for the advertising educational sector to reflect on how it might play its part in reducingstereotypical and sexist content emanating from the industry. Learning to Sell Sex(ism) will be of interest to students and scholars across a range of disciplines, including media studies, gender studies, sociology, cultural studies and marketing.
1. Introduction -- 2. Gendered advertising: From text to industry to classroom -- 3. We're just different (but equal): Unpacking students' gendered views -- 4. The reverse stereotype and the double standard: Expressions of concern about advertising's treatment of men -- 5. The Catch-22 of advertising practice (and other deflections): Perceived challenges to creating less sexist content -- 6. Conclusions and Reflections.
Keywords: Sex; Marketing; Gender Studies; Marketing